THE EFFECT OF FINANCIAL INCLUSION AND FINANCIAL LITERACY ON MSME FINANCIAL PERFORMANCE - Andini Nurwulandari (INFOKUM, 2022)
The purpose of this research is to examine how MSMEs' financial success is affected by the presence or absence of financial inclusion and financial literacy. Purposive sampling was used to choose 100 SMEs from the Bekasi Regency for this study. Multiple linear regression was used to evaluate the data gathered from the surveys. The study's findings demonstrate that MSMEs can benefit from both financial inclusion and financial literacy. For micro, small, and medium-sized enterprises (MSMEs), financial inclusion means having greater access to financing and other financial services in order to boost their financial performance. Meanwhile, financial literacy strengthens MSME's understanding of financial management, so that it can assist in managing finances and improving their financial performance. This research has implications for the government, regulators and financial institutions to increase financial inclusion and financial literacy among MSMEs. The government and regulators can help increase MSMEs' access to financial services through policies and regulations that support financial inclusion. Meanwhile, financial institutions can increase MSME financial literacy through targeted financial education and training.